Writing high-quality medical publications : a user's manual - Gutkin, Stephen W; Taylor and Francis (Boca Raton, FL : CRC Press, an imprint of Taylor and Francis, 2018)
The imperative to "publish and not perish" has never been more compelling. Yet millions of manuscripts are prepared each year without a clear path to publication by a peer-reviewed medical journal. Enter "The Gutkin Manual." Drawing from the author's distinguished, nearly 30-year career, this comprehensive and supportive guide helps to get your paper accepted$1 (Band by the journal of first choice. Elucidating pivotal principles of quality, and biostatistics, and informed by the belief that your writing can be engaging, elegant, and memorable$1 (Bno matter how technical and complex the subject matter, this volume can be your trustworthy companion as you seek to enhance both the structure and substance of your manuscripts.s
chapter 1 Principles and examples of quality in medical communications -- chapter 2 Drafting the manuscript: Step-by-step guidelines and exercises -- chapter 3 Biostatistics: Issues in study design, analysis, and reporting -- chapter 4 Best practices: Consensus recommendations and standards to prepare high-quality, ethical, transparently disclosed manuscripts for journal publication.
Keywords: MEDICAL / Allied Health Services / General; MEDICAL / Nursing / General; MEDICAL -- Allied Health Services -- General; MEDICAL -- Nursing -- General